(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article discusses a system of methodological techniques for modeling and organizing foreign language communication in classrooms; an attempt is made to consider oral communication from the point of view of activity theory; Based on the study of the nature and structure of verbal communication, oral communication is differentiated at various levels.